THE EFFECT OF THE USE OF ARTIFICIAL INTELLIGENCE TECHNOLOGY AND INFLUENCER MARKETING IN AFFILIATE MARKETING ON THE BUYING INTEREST OF GENERATION Z - Shania Salsa Bella; Ahmad Saifurriza Effasa; Ari Kuntardina (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to analyze the effect of the use of artificial intelligence technology and influencer marketing in affiliate marketing on buying interest of Generation Z. This study uses a quantitative associative causal approach with a purposive sampling technique, a sample of 100 respondents, the population in this study is Generation Z in Bojonegoro City who actively shop online through affiliate marketing and are influenced by AI and Influencer technology. Data collection was carried out through a questionnaire compiled using a five-value likert scale. Data analysis was carried out using the PLS-SEM method using SmartPLS 3 software. The results showed that influencer marketing had a significant effect on affiliate marketing and buying interest, while the use of AI did not show a significant effect on affiliate marketing or buying interest directly. Affiliate marketing also had no significant effect on buying interest as an intervening variable. This study emphasizes the importance of the role of influencers in increasing buying interest of Generation Z.